Building Blocks of Hybrid Perovskites: A Photoluminescence Study of Lead‐Iodide Solution Species. Issue 20 (30th September 2020) - Shargaieva, Oleksandra; Kuske, Lena; Rappich, Jörg; Unger, Eva; Nickel, Norbert H.
Abstract: In this work, we present a detailed investigation of the optical properties of hybrid perovskite building blocks, [PbI2+n ] n−, that form in solutions of CH3 NH3 PbI3 and PbI2 . The absorbance, photoluminescence (PL) and photoluminescence excitation (PLE) spectra of CH3 NH3 PbI3 and PbI2 solutions were measured in various solvents and a broad concentration range. Both CH3 NH3 PbI3 and PbI2 solutions exhibit absorption features attributed to [PbI3 ] 1− and [PbI4 ] 2− complexes. Therefore, we propose a new mechanism for the formation of polymeric polyiodide plumbates in solutions of pristine PbI2 . For the first time, we show that the [PbI2+n ] n− species in both solutions of CH3 NH3 PbI3 and PbI2 exhibit a photoluminescence peak at about 760 nm. Our findings prove that the spectroscopic properties of both CH3 NH3 PbI3 and PbI2 solutions are dominated by coordination complexes between Pb 2+ and I − . Finally, the impact of these complexes on the properties of solid‐state perovskite semiconductors is discussed in terms of defect formation and defect tolerance. Abstract : The optical properties of hybrid perovskite „building blocks" – polyiodide plumbates ([PbI2+n ] n− ) – formed in solutions of CH3 NH3 PbI3 and lead iodide are studied. This study provides a deep insight into the fundamental driving forces for [PbI2+n ] n− formation in both solutions and a better understanding of the role of [PbI2+n ] n− solution complexes in „defect tolerance" of hybrid perovskites.